NITRATE REMOVAL BY ELECTRODIALYSIS FROM BRACKISH GROUNDWATER: EFFECTS OF PROCESS PARAMETERS - MEDINA COLLANA, JUAN T. (2024)
A LARGE PART OF THE WORLD'S POPULATION IS SUPPLIED WITH DRINKING WATER FROM SUBWAY SOURCES. DURING THE LAST FEW YEARS, GROUNDWATER NITRATE CONCENTRATIONS HAVE INCREASED CONSIDERABLY. THIS WORK PROPOSES THE REMOVAL OF NITRATES FROM BRACKISH GROUNDWATER AND A MODEL SOLUTION BY ELECTRODIALYSIS. TO EVALUATE THEIR EFFECT ON NITRATE REMOVAL AND ENERGY CONSUMPTION, THREE FACTORS WERE SELECTED WITH THREE LEVELS FOR EACH: NITRATE ION CONCENTRATION (50, 200 AND 500 MG/L), APPLIED ELECTRICAL POTENTIAL (5, 10 AND 15 V) AND FEED FLOW ARRANGEMENT (A, B AND C). THE RESULTS SHOWED THAT THE MOST INFLUENTIAL VARIABLE WAS THE ELECTRICAL POTENTIAL, THE INCREASE OF THE POTENTIAL (15 V) LED TO A CONSIDERABLE INCREASE IN NITRATE REMOVAL (92.5 %). THE BEST CONDITIONS FOR NITRATE REMOVAL FROM THE SYNTHETIC SOLUTION WERE AT AN ELECTRICAL POTENTIAL OF 15 VOLTS, INITIAL NITRATE CONCENTRATION 200 MG/L AND THE FLOW ARRANGEMENT (C) ACHIEVING AN AVERAGE NITRATE REMOVAL OF 80%. NITRATE REMOVAL INCREASED MODERATELY WITH THE ADDITION OF THE VENTURI TUBE AND EVEN MORE WITH THE ADDITION OF AN AIR FLOW. IN ADDITION, A NITRATE REMOVAL OF 44.43% OF BRACKISH GROUNDWATER HAS BEEN ACHIEVED DURING 120 MINUTES OF TREATMENT WITH AN ELECTRICAL POTENTIAL OF 15 V AND THE ADDITION OF AIR. ENERGY CONSUMPTION VARIES BETWEEN 0.2 AND 3.17 KWH/M3 OF SOLUTION. IN CONCLUSION, ITS EFFECTIVENESS AS A DESALINATION AND DENITRIFICATION PROCESS AND ITS ENVIRONMENTAL ADVANTAGES OVER CONVENTIONAL METHODS ARE HIGHLIGHTED. © 2024, AIDIC SERVIZI S.R.L.